منهج القرآن الكريم في إدارة السلوك الإنساني: دراسة تحليلية = The Qur’anic Approach in Managing Human Behaviour: An Analytical Study - Elatrash, Radwan Jamal Yousef; Fatah Yasin, Raudlotul Firdaus (IIUM Press, 2022)
على الرغم من كثرة الجهود والدراسات العلمية حول السلوكيات العامة ومبادئ الأخلاق الإنسانية في كتب التزكية، فإن هناك نقص شديد في دراسات فهم دوافع تلك السلوكيات من المنظور القرآني، ولهذا ثارت بشأن دوافع السلوك الإنساني عدة إشكاليات عند علمائنا المسلمين. لذا يهدف هذا البحث إلى إثارة بعض المواد الخفية عن السلوك الإنساني والكشف عن أبعاد المنهج القرآني في إدارته. ويحاول هذا البحث أن يضيف لبنة جديدة إلى جهود من سبق في هذا المجال من خلال الاستقصاء والتركيز على الإطار المنهجي للقرآن الحكيم في نظرته لدوافع السلوك الإنساني، ونظرة المفسرين القدامى والمحدثين وبعض الدراسات الخاصة في علم النفس. ومن ثم اقتضت طبيعة هذا البحث الاعتماد على المنهجين الاستقرائي والوصفي والتحليلي، وذلك أنه يرتكز على ركنين هما: إظهار معالم الإدارة القرآنية للسلوك الإنساني، والحديث عن السلوك الإنساني وإبراز أنواعه وتداعياته كما تحدث عنه القرآن الكريم، من أجل الوصول إلى نتائج مهمة وعلى رأسها: أن القرآن من أعظم المصادر الإدارية التي تحدثت عن السلوك الإنساني ودوافعه. وأن القرآن الحكيم أظهر أن السلوك الإنساني ينقسم إلى قسمين رئيسين باعتبار دوافعهما: فهناك دوافع صالحة، ودوافع شريرة. كما أثبت البحث أن القرآن أظهر أن هناك ارتباطاً وثيقاً بين السلوك الإنساني وبين قناعاته ومعتقداته، وأن الانحراف السلوكي دليل على عدم اكتمال الإيمان في النفوس. Despite a large number of efforts and scientific studies on general behaviors and the principles of human ethics in the books of Tazkiyat Al-Nafs (purification of the self'), studies on understanding the motives for these behaviors are severely lacking, and this is why several problems arose about the motives of human behavior among our Muslim scholars. That is why this research aims to raise some hidden materials about human behavior and to reveal the dimensions of the Qur’anic approach in its management. This study attempts to add a new building block to the efforts of those who preceded in this field through investigation and focus on the methodological framework of the wise Qur’an in its view of the motives of human behavior, the view of ancient and modern commentators, and some special studies in psychology. The nature of this research requires reliance on inductive, descriptive, and analytical methods. The article is based on two pillars: showing the features of the Quranic management of human behavior, and the second pillar: it specializes in talking about human behavior and highlighting its types and repercussions. In order to reach important results, chief among them: is that the Qur’an is one of the greatest sources that talk about human behavior and its motives. And that human behavior is divided into two main parts, considering their motives: there are good motives and evil motives. There is also a close link between human behavior and convictions and beliefs, and behavioral deviation is evidence of incomplete faith in the soul.